Penilaian Kinerja Keuangan Pada Koperasi Simpan Pinjam Mitra Usaha Desa Bungaya Karangasem - Ni Nyoman Ari Natarini (Global Researcher Network, 2021)
This research was conducted to analyze the financial performance of the Bungaya Village Business Partners' Savings and Loans Cooperative for the period 2012-2016 in terms of the Health Assessment Guidelines for Savings and Loans Cooperatives and Cooperative Savings and Loans Units based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06 / Per. /Dep.6/IV/2016. Collecting data in this study using documentation and interview methods. Data analysis in this study uses financial performance assessment variables measured by six aspects, namely capital, earning asset quality, management, efficiency, liquidity, and independence and growth in accordance with the Regulation of the Deputy for Supervision of the Ministry and Small and Medium Enterprises of the Republic of Indonesia Number 06 / Per. /Dep.6/IV 2016. Based on the analysis that has been done, the financial performance of the KSP. Bungaya Village Business Partners in 2012-2016 in terms of six aspects, namely the aspect of capital, quality of productive assets, aspects of management, aspects of efficiency, aspects of liquidity and aspects of independence and growth received the predicate